Staging cardiac damage in aortic valve disease: one size fits all?. (14th October 2021) - Silva, G; Sampaio, F; Espada Guerreiro, C; Goncalves Teixeira, P; Ribeiro Queiros, P; Ribeiro Da Silva, M; Brandao, M; Ferreira, D; Fontes-Carvalho, R
Abstract: Background: Nowadays, in patients with aortic regurgitation (AR), aortic valve surgery is indicated when severe and symptomatic or those with depressed LVEF. However, clinical outcomes of patients with significant aortic regurgitation are not influenced by these factors only. Recently, a new staging system for severe aortic stenosis has been proposed by Généreux on the basis of the extent of anatomic and functional cardiac damage. If this model could be applicable to an unselected significant AR population has not been tested. Purpose: The aim of our study was to evaluate the prevalence of the different stages of extra-aortic valvular cardiac damage by the application of Généreux staging and its impact on prognosis in a large, real world cohort of significant AR patients. Methods: This study retrospectively analysed the clinical, Doppler echocardiographic and outcome data in patients with grade III or greater AR between January 2014 and September 2019. According to the extent of cardiac damage on echocardiography, patients were classified as Stage 0 (no cardiac damage), Stage 1 (left ventricular damage), Stage 2 (mitral valve or left atrial damage), Stage 3 (tricuspid valve or pulmonary artery vasculature damage) or Stage 4 (right ventricular damage). Exclusion criteria were severe aortic stenosis and previous valve repair or replacement. The primary end-point was all-cause mortality. Results: A total of 572 patients, aged 70.1±13.9 years, 294 (51.3%) men were enrolled. One third of patients were in NYHA I. Based on the proposed classification, 82 patients (14.3%) were classified in stage 0, 130 (22.7%) in stage 1, 276 (48.2%) in stage 2, 68 (11.8%) in stage 3 and 17 (3.0%) in stage 4. Median follow-up time was 3.3±1.9 years. There was a progressive increase in mortality rates according to staging: 8.5% in stage 0, 10.8% in stage 1, 24.9% in stage 2, 42.6% in stage 3 and 52.9% in stage 4 (p<0.001). On multivariable analysis, the extent of cardiac damage was independently associated with excess mortality (HR 1.69, 95% CI 1.29 to 2.21) Conclusion: Our study demonstrated that this new staging system studied for aortic stenosis also provides increased prognostic value to patients with significant aortic regurgitation. This staging system can be helpful to identify the degree of extra-aortic valvular cardiac damage and to optimize the time of valvular intervention. Further prospective studies are needed to confirm the benefit of the applicability of this model in clinical practice. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Centro Hospitalar Vila Nova de Gaia / Espinho